ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM PENGELOLAAN PROGRAM BANTUAN OPERASIONAL KESEHATAN (BOK) DI PUSKESMAS JALAN KEMBANG - Suripto Suripto; Rahmawati Rahmawati (FEB Institut Bakti Nusantara, 2022)
The rapid advancement of information technology today makes most people increasingly feel that information is one of the most important needs. Likewise, in an agency, an information system is nedeed. The objectives of the research are to find out how to apply accounting information systems in management of the BOK program at Jalan Kembang Health Center, and to determine the effectiveness of tha application of the information system. The research method used by the author is a descriptive research method. The conclusion from the results of the research conducted by the author is that the application of an accounting information system at Jalan Kembang Health Center has implemented the system in accordance with exissting produceres. It’s just that there are a few shortcomings, namely in there effectivenes in collecting reports, they always experience delays and also lack of employees to complete reports.